1993
DOI: 10.1063/1.352924
|View full text |Cite
|
Sign up to set email alerts
|

Probe diagnostics of non-Maxwellian plasmas

Abstract: Various probe diagnostic methods have been applied to rf plasmas with non-Maxwellian electron energy distribution functions (EEDF) and the results of these diagnostic methods have been compared. Plasma density and electron temperature were obtained using standard procedures from the electron retardation region (classic Langmuir method), the ion saturation region, and the electron saturation region of the measured probe I/V characteristic. Measurements were made in a 13.56-MHz capacitive argon rf discharge at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
200
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(207 citation statements)
references
References 8 publications
7
200
0
Order By: Relevance
“…Sheridan et al 51 reported them for dc discharges in helium and Godyak et al 52 analyzed different non-Maxwellian plasmas with probe diagnostics. In the field of pulsed plasmas, Bäcker and Bradley 37 thoroughly investigated the effects of incorporating magnetrons into the plasma parameters, such as, for instance, the generation of bi-Maxwellian discharges induced by the presence of a magnetic field.…”
Section: ͑7͒mentioning
confidence: 99%
“…Sheridan et al 51 reported them for dc discharges in helium and Godyak et al 52 analyzed different non-Maxwellian plasmas with probe diagnostics. In the field of pulsed plasmas, Bäcker and Bradley 37 thoroughly investigated the effects of incorporating magnetrons into the plasma parameters, such as, for instance, the generation of bi-Maxwellian discharges induced by the presence of a magnetic field.…”
Section: ͑7͒mentioning
confidence: 99%
“…As it has been described in §IV about the ionic part of the I-V characteristic, we fit the data to equation (16) determining the values for the constants γ, β and C 0 . These values are summarized in Table 1.…”
Section: Least-squares Fittingmentioning
confidence: 99%
“…Considering this value for the temperature T e , we find by equation (21) the density n e = 1.62 × 10 16 m −3 . For the values computed after fitting, it is possible to accomplish the integration of the adjusted characteristic, to obtain [15,16] …”
Section: Least-squares Fittingmentioning
confidence: 99%
“…This analysis will provide accurate determination of the lower temperature distributions but for the highest energy distribution the measured temperature can be, and often is, inaccurate. 4 This inaccuracy arises since the electron current becomes increasingly sensitive to the removal of the ion saturation current as the high energy tail of the distribution function becomes more depleted. That is, the determination of the electron temperature becomes increasing inaccurate as the electron energy distribution function moves from a Maxwellian type distribution towards a mono-energetic distribution.…”
Section: Introductionmentioning
confidence: 99%